Análisis Financiero del Gobierno Autónomo Descentralizado Municipal del Cantón Puyango, periodo 2021-2022 - Ortiz Dávila, Ana María (2024)
Financial analysis is a key tool that enables various public and private enterprises and institutions to assess their economic and financial status, aiming at facilitating informed decision- making and correcting errors that may hinder the normal development of their activities. This underscores the importance of its application. The research aimed to determine the economic and financial structure of the Municipal Administration of Puyango, employing both qualitative and quantitative approaches through inductive, deductive, and mathematical methods. Financial statements of the Municipal Administration of Puyango for the period 2021-2022 were analyzed, with the data provided by the institution's financial director. Using vertical and horizontal analysis, it was determined that the highest concentration of assets is in fixed assets, primarily financed through public debt acquisition. Implementation of management and budget indicators revealed suboptimal levels of effectiveness in revenues and expenditures, along with a stable solvency level that heavily relies on transfers from the Central Administration to fulfill its obligations. Conclusions indicate that the majority of assets are concentrated in fixed assets, accounting for 60% of institutional resources, which have been allocated to long-term investments. Liabilities increased by 26% between periods, corresponding to credit acquisitions benefiting the institution, while management expenses, comprising 69% of total expenditures, are driven by public investments. Furthermore, the municipal entity exhibits a suboptimal level of self-sufficiency and financial autonomy.